Effects of CYP2C19*17 genetic polymorphisms on plasma and saliva concentrations of diazepam in patients with alcohol withdrawal syndrome. (6th January 2022) - Skryabin, Valentin Yurievich; Zastrozhin, Mikhail; Torrado, Marco; Grishina, Elena; Ryzhikova, Kristina; Shipitsyn, Valery; Galaktionova, Tatiana; Bryun, Evgeny; Sychev, Dmitry
Abstract : Introduction: Diazepam is one of the most commonly prescribed tranquilizers for the therapy of alcohol withdrawal syndrome (AWS). However, diazepam therapy often turns out to be ineffective, and some patients experience dose-dependent adverse drug reactions. Previous studies have shown that the metabolism of diazepam involves the CYP2C19 isoenzyme, whose activity is highly dependent on polymorphism of the encoding gene. Objective: The study aimed to investigate the effects of CYP2C19*17 genetic polymorphisms on plasma and saliva concentrations of diazepam as well as its impact on the efficacy and safety rates of therapy in patients with AWS. Material and methods: The study was conducted on 100 Russian male patients suffering from the AWS who received diazepam injections at a dosage of 30.0 mg/day for 5 days. Genotyping was performed by real-time PCR with allele-specific hybridization. The efficacy and safety assessment was performed using psychometric scales. Results: Based on the results of the study, we revealed differences in the efficacy and safety of therapy in patients with different CYP2C19 -806C>T genotypes. Therapeutic drug monitoring revealed the statistically significant difference in the levels of diazepam plasma concentration: ( CC ) 251.76 (214.43; 310.61) vs. ( CT+TT ) 89.74 (54.18; 179.13); P  = 0.003, and diazepam saliva concentration: ( CC ) 3.86 (3.22; 5.12) vs. ( CT + TT ) 0.79 (0.44; 1.56); P  = 0.003. Conclusion: Our study showed the effects of CYP2C19*17 genetic polymorphisms on the efficacy and safety rates of diazepam. Furthermore, we revealed the statistically significant differences in plasma and saliva concentration levels of diazepam in patients carrying different genotypes.